Analisis Bentuk dan Struktur Lagu Genit Karya Tipe-X: Sebuah Tinjauan Musikologis - Muhamad Ihsan Alamsyah; Jagar Lumbantoruan (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2022)
Genit is a work of music popularized by a local Indonesian music group, type-x. This work is very interesting to study in the perspective of musicology because there are so many ornaments that are the character of the Type-X music group. This study aims to analyze the shape and structure of a song called flirtatious by a Type-X music group. The research conducted is qualitative research with a systematic textual analysis approach, objectivity, and generalization using a musicological approach. This research data was collected from literature study activities, observations, and labor work. Data analysis is carried out by means of data reduction, data analysis and drawing conclusions. Based on the analysis of flirty songs by type-x, it is concluded that the form of the song consists of two parts, namely (A-B) which is carried out by the development of the period, namely (A, A', B' A1). In detail the phrases in each period are A(a-a') A'(a-x) B(y-z) A1(a-b) with a sum of 4 antecedent phrases and 4 consequent phrases. The motifs contained in the flirty song there are 10 motifs with the processing of motifs in literal repetition, inversion, interval reduction, reduction of tone values and enlargement of tone values, the motifs are m, n, m1, n', p, q, r, p1, r1, x. The lyrical relationship form in this song is dominated by the relationship form silabik with one word representing one note.